2016
DOI: 10.5330/1096-2409-20.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Play Therapy Intervention on Children's Externalizing and Off-Task Behaviors

Abstract: Children's externalizing and off-task behaviors are deemed a major concern for elementary teachers and interfere with the classroom learning environment (Abidin & Robinson, 2002; Shillingford-Butler & Theodore, 2013). Children with these behaviors are at risk of falling behind academically and experiencing ongoing behavioral problems throughout their development. This single-case research design investigates the effectiveness of Adlerian play therapy on the behaviors of two elementary-aged children who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Another indication of efficacy in play therapy not mentioned in Figure 4 is related to the treatment demand from clients .Various studies show that play therapy can be an effective intervention for issues in the areas of emotional growth and externalizing behavioural problems (Ritzi et al. 2017 ; Meany-Walen 2017 , Meany-Walen et al. 2015 ; Landreth et al.…”
Section: Resultsmentioning
confidence: 99%
“…Another indication of efficacy in play therapy not mentioned in Figure 4 is related to the treatment demand from clients .Various studies show that play therapy can be an effective intervention for issues in the areas of emotional growth and externalizing behavioural problems (Ritzi et al. 2017 ; Meany-Walen 2017 , Meany-Walen et al. 2015 ; Landreth et al.…”
Section: Resultsmentioning
confidence: 99%
“…This preference might be especially true in settings where there are limited treatment providers in relationship to the number of children in need of services, such as in schools, where the average student-to-counselor ratio is much higher than is the recommended ratio (American School Counseling Association [ASCA], 2016, n.d.). Group Adlerian play therapy (GAdPT), which combines tenets from both AdPT and group therapy, provides opportunities for children to express themselves, learn about themselves and others, and practice socially advantageous behaviors through the use of toys and creative media within the group setting (Kottman, 2011; Meany-Walen, Bullis, Kottman, & Dillman Taylor, 2015; Meany-Walen et al, 2017; Sweeney, Baggerly, & Ray, 2014). Woolf (2011) found that children who participate in group counseling interventions that utilize play therapy techniques demonstrate improvements in social, emotional, and behavioral learning.…”
Section: Play Therapymentioning
confidence: 99%
“…Results revealed statistically significant findings: Treatment group children demonstrated improved classroom behaviors, and teachers stress in relationship to the treatment group children was reduced. Additional empirical support for AdPT has been provided through single-case design (SCD) studies with individuals (e.g., Akay, 2013; Dillman Taylor & Meany-Walen, 2015; Meany-Walen et al, 2015) and four studies that utilized GAdPT (Kottman & Meany-Walen, 2016; Meany-Walen et al, 2015, 2017; Stutey, Dunn, Shelnut, & Ryan, 2017). The listed studies demonstrated overall positive results for AdPT (group and individual) with elementary-age children’s behaviors.…”
Section: Adlerian Play Therapy Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Group AdPT has shown success in a number of single case designs in which Group AdPT was the independent variable (e.g., Dillman Taylor, Meany-Walen, Nelson, & Gungor, in press; Meany-Walen et al, 2015; Meany-Walen & Teeling, 2016; Meany-Walen, Teeling, Davis, Artley, & Vignovich, 2018; Stutey, Dunn, Shelnut, & Ryan, 2017). In many of these cases, treatment was deemed effective in a shorter number of sessions than in research in which participants received individual sessions.…”
Section: Group Adptmentioning
confidence: 99%